Analysis of structure of the biathlon runs - Colewa, J.; Gerasimuk, D.; Szepelawy, M.; Zajac, A. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2005)
The biathlon is an Olympic sport discipline, which is a combination of two events, Nordic skiing and precision shooting. Combining events of such different psychophysical background creates great demands on the athlete and coach. The main objective of this paper was to determine which of these events has a greater impact on the final result considering the distance and sports level. The results of the World Cup and the Olympic Games in the 2001/02 season were analyzed statistically. The data indicates that he results of the run influence the final result to a higher degree than shooting does. This is especially true in the sprint and in relation to biathletes of higher sports level. At long distances, the level of shooting and the time of the run influence the final result to the same extent. The influence of the time of shooting on the final result is dependent on the distance of the run.